Shining light on knee osteoarthritis: an overview of vitamin D supplementation studies - Di Zhang; Miaoyu Ye; Yao Xu; Luyu Jiang; Yanmei Hu; Qi Zhang; Xiao Han; Qian Dai; Junhui Qian; Jian Luo; Qiang Yuan (Frontiers in Medicine)
BackgroundThe impact of knee osteoarthritis on individuals’ daily functioning is significant. In recent years, Vitamin D supplements cure osteoarthritis has garnered attention from medical professionals and patients due to its simplicity and portability. Several systematic reviews (SRs) and meta-analyses (MAs) have examined the efficacy of vitamin D supplementation for knee osteoarthritis, yet there is variability in their methodology and quality.ObjectiveTo search, gather, and analyze data on the characteristics and quantitative results of SR/MA in patients with KOA treated with Vitamin D supplementation, and objectively evaluate the efficacy of supplements. Then, provides clinical evidence and recommendations the clinical use of vitamin D supplementation.MethodsTwo individuals reviewed and collected data from four databases until October 2023. AMSTAR-2, ROBIS, PRISMA 2020, and GRADE tools were used to evaluate the methodological quality, bias risk, reporting quality, and evidence strength of all SR/MA. Additionally, we applied the corrected covered area (CCA) method to measure overlap in randomized controlled trials (RCTs) cited among the SR/MA.Results3 SRs and 6 MAs were included in the analysis: 3 studies were low quality by AMSTAR-2, and 6 studies were very low quality. According to ROBIS, 6 studies were high-risk and 3 were low-risk. In PRISMA 2020 reporting quality, most studies showed deficiencies in comprehensive literature search strategy, reasons for literature exclusion, data preprocessing for meta-analysis, exploration of reasons for heterogeneity, sensitivity analysis, publication bias, and disclosure of funding and conflicts of interest. Grading the quality of evidence in GRADE consisted of 5 items of moderate quality, 14 items of low quality, and 10 items of very low quality. Bias risk and imprecision were the main factors for downgrading. The calculation of RCT overlap between SR/MA using CCA showed a high degree of overlap.ConclusionVitamin D supplementation may show potential efficacy in ameliorating symptoms of KOA. The evidence indicates that Vitamin D supplements for knee osteoarthritis can improve patients’ Total WOMAC scores and synovial fluid volume in the joints. Nevertheless, due to the generally low quality of current studies, future research should prioritize improving the quality of primary studies to establish the efficacy of vitamin D supplementation for KOA with more robust scientific evidence.Systematic review registrationThe protocol of this overview was registered in the International Prospective Register of Systematic Reviews (PROSPERO) (https://www.crd.york.ac.uk/PROSPERO/) with the registration number CRD42024535841.